2013
DOI: 10.1088/0004-637x/777/1/54
|View full text |Cite|
|
Sign up to set email alerts
|

DISSOCIATIVE RECOMBINATION MEASUREMENTS OF HCl+ USING AN ION STORAGE RING

Abstract: We have measured dissociative recombination of HCl + with electrons using a merged beams configuration at the heavy-ion storage ring TSR located at the Max Planck Institute for Nuclear Physics in Heidelberg, Germany. We present the measured absolute merged beams recombination rate coefficient for collision energies from 0 to 4.5 eV. We have also developed a new method for deriving the cross section from the measurements. Our approach does not suffer from approximations made by previously used methods. The cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…This can be seen in Figure 1, which presents the fit using Equation (3) to the O'Connor et al (2015) data minus their actual data, normalized by their results (i.e., the normalized residuals). These findings continue the trend seen in merged-beams astrochemical studies that the Arrhenius-Kooij formula does a poor job in reproducing the experimentally derived rate coefficients for barrierless exoergic reactions, as has been seen for associative detachment (Kreckel et al 2010), dissociative recombination (Novotný et al 2013(Novotný et al , 2014, and proton and H In the absence of any deep theoretical understanding of Reactions (1) and (2), it is not clear what fitting formula to use. We have opted to use the versatile fitting function recommended by Novotný et al (2013) for astrochemical modeling, namely,…”
Section: Fitting the Experimental Resultssupporting
confidence: 61%
“…This can be seen in Figure 1, which presents the fit using Equation (3) to the O'Connor et al (2015) data minus their actual data, normalized by their results (i.e., the normalized residuals). These findings continue the trend seen in merged-beams astrochemical studies that the Arrhenius-Kooij formula does a poor job in reproducing the experimentally derived rate coefficients for barrierless exoergic reactions, as has been seen for associative detachment (Kreckel et al 2010), dissociative recombination (Novotný et al 2013(Novotný et al , 2014, and proton and H In the absence of any deep theoretical understanding of Reactions (1) and (2), it is not clear what fitting formula to use. We have opted to use the versatile fitting function recommended by Novotný et al (2013) for astrochemical modeling, namely,…”
Section: Fitting the Experimental Resultssupporting
confidence: 61%
“…If we now disregard the large N N (H Cl ) (H) 2 + ratio reported for W31C, the maximum discrepancy between theory and observation is reduced from the factor ∼10 discussed in Paper I to a factor ∼5. Moreover, since the publication of Paper I, Novotný et al (2013) have reported a laboratory measurement of the rate coefficient for DR of HCl + , a key intermediary in the primary production pathway for chloronium: Cl(h , e) n Cl (H , H)HCl (H , H)H Cl 2 2 2 + + + . The measured value is smaller than that adopted by NW09 by a factor of 1.5 at 10 K and 3 at 300 K. Since the DR of HCl + limits the availability of HCl + to form H Cl 2 + , a downward revision in the adopted rate coefficient would increase the predicted H Cl 2 + abundances; however, the dependence is a relatively weak one, in that a factor 10 reduction in that rate coefficient was found to increase the H Cl 2 + abundance by only a factor of 1.3 (Paper I).…”
Section: Resultsmentioning
confidence: 99%
“…Applying the recently established procedure [8] the measured mb (E d ) is fitted by the sum of a large number of individual signals, each assuming a constant cross section contribution stemming from a narrow energy bin only. The energy binning for these contributions is adapted to the measured structures and the contribution magnitudes are found so that their superposition optimally fits the measured data.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work [8] the determination of (T e ) from the measured merged-beams rate coefficient mb (E d ) was re-considered taking into account the high-resolution energy dependence of these experimental results. The method was applied to the DR rate of HCl + , where it revealed significant deviations from the T −1/2 e power law dependence for (T e ).…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%